Reliabilitas Pengukuran Flexible Curve pada Kurva Thoracal di RS Efarina Berastagi - Ginting, Isaharpika Br; Purba, Yeni Trisna; Sinaga, Fransius P. (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2025)
The sagittal plane curve in the thoracal region is one of the indicators for assessing the overall vertebral curve. Abnormalities in the sagittal plane have an impact not only on the vertebrae, but also posture. The measurement of sagittal plane curves should be carried out using measuring instruments that meet the psychometric aspects of the study. The purpose of this study is to determine the consistency or reliability of measurements using flexible curves. This type of research is to take repeated measurements by two physiotherapists. The sample in this study was 8 people who met the inclusion criteria. The reliability test results were carried out using intraclass correlation obtained a value of 0.847. The conclusion of this study is that there is a high reliability in the flexible curve to measure the thoracal curve.